Relationship between endoparasitism, body condition and blood biochemistry in Peruvian spider monkeys (ateles chamek) at the Taricaya Rescue Center, Madre de Dios, Peru - Salazar, Michelle (2021)
Ateles chamek (Humboldt, 1812) is an "Endangered" species and is included in Appendix II of CITES, due to poaching for illegal trade and deterioration of its habitat. For this reason, rescue centres have been created for their protection and, if possible, return to their natural environment; however, captivity, feeding and handling can promote the development of parasitosis. The aim of the present study was to determine the relationship between endoparasitism, blood biochemistry and body condition in 20 individuals of the species A. chamek from the Taricaya Rescue Center, Madre de Dios. Stool and blood samples were taken during the sanitary control. Body condition was determined using a score based in Macaca mulata primates. The faeces were processed with the flotation method in a salt and sugar solution; and the blood plasma was analysed with a biochemical processor. The stool analysis found Strongyloides sp (1/20), Molineus sp (1/20), Ascaris sp (1/20), Physaloptera sp (1/20), Trichuris sp (1/20), Entamoeba sp (1 / 20), Giardia sp (3/20) and an unidentified ascaroid nematode (1/20). Glucose values were 97.8 ± 12.1 mg / dl, total protein 7.09 ± 0.337 g / dl, total bilirubin 0.12 ± 0.0219 mg / dl and albumin 5.47 ± 0.416 g / dl. The body condition was 2.3 ± 0.219. No significant association was found between the variables under study with parasitosis.